Aerothermodynamic Optimization of Aerospace Plane Airfoil Leading Edge - Zhou,Chen (2017)
ABSTRACT: Aiming to mitigate the aerodynamic heating during hypersonic re-entry, the aerothermodynamic optimization of aerospace plane airfoil leading edge is conducted. Lift-to-drag ratio at landing condition is taken as a constraint to ensure the landing aerodynamic performance. First, airfoil profile is parametrically described to be more advantageous during the optimization process, and the Hicks-Henne type function is improved considering its application on the airfoil leading edge. Computational Fluid Dynamics models at hypersonic as well as landing conditions are then established and discussed. Design of Experiment technique is utilized to establish the surrogate model. Afterwards, the previously mentioned surrogate model is employed in combination with the Multi-Island Genetic Algorithm to perform the optimization procedure. NACA 0012 is taken as the baseline airfoil for case study. The results show that the peak heat flux of the optimal airfoil during hypersonic flight is reduced by 7.61% at the stagnation point, while the lift-to-drag remains almost unchanged under landing condition.